The Concept of a Country According To Thought Ibn Bājjah in The Book Tadbīr Al-Mutawaḥḥid: Konsep Negara Menurut Pemikiran Ibn Bājjah Dalam Kitab Tadbīr Al-Mutawaḥḥid - Januarti, Putri; Lestari, Ayu; al-Walid, Khalid (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
The role of the state in politics is a very complex and interesting issue, especially because the concept of the state has varied meanings and interpretations among experts. Ibn Bājjah, also known as Avempace, was a Muslim philosopher and scientist from western Andalusia who lived in the 11th century. His contribution to Islamic political thought is mainly reflected in his work entitled